Online skill based assessment system in recruitment and selection for UiTM networking students in the Faculty of Information Technology and Quantitative Sciences (FTMSK) using Object Oriented Hypermedia Design Method (OOHDM) / Azrina Hafizah Abdul Aziz - Abdul Aziz, Azrina Hafizah (2006)
The web is now a significant component of the recruitment and job search process. This research is conducted with the objectives to design and develop Online Skill Based Assessment System in Recruitment and Selection for UiTM Networking student in FTMSK. This project provides a platform for students who seek for jobs and recruiting companies as well as the contribution by the UiTM as intermediary between them. The design approach used in this research is Object Oriented Hypermedia Development Method (OOHDM). The data are gathered from a survey conducted in FTMSK which involved 55 students in order to capture the user requirements for this project. 83 percent of the survey participations agreed that there is no online jobs applications service available in the UiTM website. Its existence is very essential as agreed by 96 percent of the respondents. These have motivated and act as a drive for the development of Online Skill Based Assessment System which will help UiTM graduates to demonstrate their personal and professional skills to improve their chances of employment success. Besides that, it assists the companies in their recruiting efforts and selection process of hiring graduates by having collaboration with UiTM.